Abundance matters: role of albumin in diabetes, a proteomics perspective - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Venkatasubramani, Vinashya; Kulkarni, Mahesh J. (Expert Review of Proteomics, 2017)
Introduction: Human serum albumin (HSA) is a multifaceted protein with vital physiological functions. It is the most abundant plasma protein with inherent capability to bind to diverse ligands, and thus susceptible to various post-translational modifications (PTMs) which alter its structure and functions. One such PTM is glycation, a non-enzymatic reaction between reducing sugar and protein leading to formation of heterogeneous advanced glycation end products (AGEs). Glycated albumin (GA) concentration increases significantly in diabetes and is implicated in development of secondary complications. Areas covered: In this review, we discuss in depth formation of GA and its consequences, approaches used for characterization and quantification of GA, milestones in GA proteomics, clinical relevance of GA as a biomarker, significance of maintaining abundant levels of albumin and future perspectives. Expert commentary: Elevated GA levels are associated with development of insulin resistance as well as secondary complications, in healthy and diabetic individuals respectively. Mass spectrometry (MS) based approaches aid in precise characterization and quantification of GA including early and advanced glycated peptides, which can be useful in prediction of the disease status. Thus GA has evolved to be one of the best candidates in the pursuit of diagnostic markers for prediction of prediabetes and diabetic complications.

Albumin abundance and its glycation Status determine hemoglobin glycation - Jagadeeshaprasad, Mashanipalya G.; Venkatasubramani, Vinashya; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2018)
Diabetes diagnosis and management majorly depend upon the measurement of glycated hemoglobin (HbAlc) levels. Various factors influence HbAlc levels such as the use of various analytical methods and the presence of various clinical conditions. Plasma albumin levels were known to be negatively associated with HbAlc. However, the precise mechanism by which they affect HbAlc is not well' understood. Therefore, we have studied the influence of albumin levels and its glycation status on hemoglobin glycation using erythrocyte culture experiments. Erythrocytes maintained at low albumin concentration exhibited relatively increased albumin and hemoglobin glycation as compared to that in those maintained at higher albumin concentration. Increase in albumin glycation may decrease its ability to protect hemoglobin glycation. This was demonstrated by treatment of erythrocytes with N(epsilon-(carboxymethyl)lysine-modified serum albumin (CMSA), which failed to protect hemoglobin glycation; instead, it increased hemoglobin glycation. The inability of CMSA to reduce hemoglobin glycation was due to the lack of free lysine residues of albumin, which was corroborated by using N(epsilon-(acetyI)lysine serum albumin (AcSA) and clinical diabetic plasma. This is the first study which demonstrates that the modification of lysine residues of albumin impairs its ability to inhibit hemoglobin glycation. Furthermore, correlation studies between HbAlc and albumin levels or relative albumin fructosamine from clinical subjects supported our experimental finding that albumin abundance and its glycation status influence hemoglobin glycation. Therefore, we propose albumin level and its glycation status to be quantified in conjunction with HbAlc for better management of diabetes.